PENGGUNAAN GELOMBANG AKUSTIK PADA PROSES PEMISAHAN PARTIKEL PENGOTOR DALAM AIR DENGAN MENGGUNAKAN TABUNG RESONANSI - Lifa Anggar Mayasari; Defrianto '; Riad Syech (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research has been done on the use of acoustic waves in order to separate pollutant particles in water. This research has been performed by an experimental method utilizing the second and the third harmonic mode of acoustic waves. The results showed that the use of both modes was affected by their intensity. It was proved that the treatment of the second harmonic mode wave yielded the difference of concentration of water that depended on the intensity level ( IL ) of the wave. The value of 0.035 mg/L, 0.09 mg/L, and 0.15 mg/L have been found respectively, for the IL of 83.2 dB, 92.4 dB, and 102.3 dB by second harmonic mode treatments to the water of 0.40 mg/L. Meanwhile, the use of the third harmonic mode wave treatments to the same water samples gave the differences of concentration of 0.07 mg/L, 0.11 mg/L, and 0.17 mg/L respectively, for the ILs of 65.9 dB, 75.2 dB, and 84.8 dB. It was showed that the treatment of the third harmonic resulted bigger difference concentration of the samples. The bigger the difference concentration, the better the separation of pollutant particle in the sample. It can be concluded that acoustic waves can be used to separate the pollutant particles in water.